Immunosuppressive therapy: methodological and ethical observations - Manna, Raffaele (Medicina e Morale, 2024)
Over the past 20 years, the therapy of autoimmune diseases has undergone considerable progress. Since the initial use of corticosteroids in the treatment of rheumatoid arthritis in the late 1940s, a large number of therapeutic agents and various treatment protocols have been produced and tested.